2022
DOI: 10.48129/kjs.15261
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Javanese Turmeric (Curcuma xanthorriza Roxb) on Fibroblasts, Granulation, Blood Vessel Density, and Contraction in Wound Healing of STZ-Induced Diabetic Rats

Abstract: Diabetic ulcers usually occur in the lower extremities of diabetic patients. One in 20 diabetic patients will develop an ulcer, and 10% of those cases lead to amputation. This study aimed to investigate the effects of Javanese turmeric (Curcuma xanthorriza Roxb.) extract on the number of fibroblasts, granulation, blood vessel, and the rate of wound contraction in a Wistar rat model of the diabetic ulcer. This was an experimental study with post-test observations only and randomized control group design. Rats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…According to Mardiyantoro et al, 34 an increased number of fibroblast cells indicates an improvement in the rat sockets' wound healing process, suggesting that the 5% C. xanthorrhiza extract gel can enhance the wound healing process. Other studies, such as Kristianto's, 35 support these findings, showing a significant impact of C. xanthorrhiza extract administration on diabetic rat wound tissue, with more fibroblast cells in the treatment group than in the negative control group. The increased number of fibroblast cells is attributed to the active compounds present in the extract, such as curcumin, flavonoids, and saponins, which can enhance fibroblast cell proliferation and activate their forming factors.…”
Section: Discussionmentioning
confidence: 58%
“…According to Mardiyantoro et al, 34 an increased number of fibroblast cells indicates an improvement in the rat sockets' wound healing process, suggesting that the 5% C. xanthorrhiza extract gel can enhance the wound healing process. Other studies, such as Kristianto's, 35 support these findings, showing a significant impact of C. xanthorrhiza extract administration on diabetic rat wound tissue, with more fibroblast cells in the treatment group than in the negative control group. The increased number of fibroblast cells is attributed to the active compounds present in the extract, such as curcumin, flavonoids, and saponins, which can enhance fibroblast cell proliferation and activate their forming factors.…”
Section: Discussionmentioning
confidence: 58%
“…Curcuminoids can stimulate growth factors such as TGF-đť›˝, which play a role in early granulation tissue formation during wound healing. TGF-đť›˝ also stimulates the formation of new blood vessels, thereby expediting the wound healing process (Heri et al, 2022). Curcuminoids possess anti-inflammatory activity by inhibiting COX-2 and LOX enzymes, which are significant during the inflammation phase.…”
Section: Discussionmentioning
confidence: 99%
“…The faster the re-epithelialization process, the quicker the wound closure, leading to an expedited wound healing process. One sign of a successful re-epithelialization process is the absence of an epithelial gap or complete closure of the epithelial gap (Primadina, Basori, and Perdanakusuma, 2019;Kamal et al, 2021;Heri et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] Previous studies have stated that Curcuma xanthorrhiza extract is effective in accelerating the healing progress of a second-degree burn wound. 8,[10][11][12] In their research, 5% Curcuma xanthorrhiza extract showed a significant result with a 40% wound closure rate on the 9 th day, as proved by the formation of granulation tissue. 7 The granulation tissue is a result of fibroblast proliferation and angiogenesis, which aid in faster wound closure.…”
Section: Introductionmentioning
confidence: 99%